The The Effect of Reward and Punishment on Student Discipline in Teknomedika Plus Vocational High School - Ai Kurniasih; Qowaid Qowaid; Saepudin Saepudin (Peneliti.net, 2021)
This research is motivated by the low discipline of students in school. To overcome this, the factors that can affect student discipline are carried out. This study aims to determine the extent of reward and punishment on student discipline, especially in Teknomedika Plus Vocational High School. This research instrument uses documentary studies, observation, and questionnaires. The research method used is a descriptive quantitative method with multiple linear analysis, with purposive sampling. Quantitative analysis includes validity and reliability tests, basic assumption tests, classical assumption tests, hypothesis testing using f-table and table t-test, and the coefficient of determination (R2). The results showed that the contribution of reward (X1) and punishment (X2) on student discipline (Y) was 82.4%, and the remaining 17.6% was influenced by other variables not examined in this study. Ha is accepted. It means reward and punishment together affect student discipline